Metode TEACCH sebagai strategi pendampingan psikologis untuk meningkatkan kemandirian anak dengan spektrum autisme di UPT SDN 253 Gresik - Laili Inayah; Ima Fitri Sholichah (Journal of Profession Education, 2025)
This study aims to describe the application of the TEACCH (Treatment and Education of Autistic and Related Communication-Handicapped Children) method as a psychological mentoring strategy to foster independence among children with autism spectrum disorder (ASD) at UPT SDN 253 Gresik. Using a descriptive qualitative approach, the researcher designed and implemented a structured intervention program for a first-grade student diagnosed with ASD, based on observations, interviews, and documentation. The TEACCH-based intervention focused on structured learning environments, visual schedules, and individualized education programs (IEPs). The findings showed that TEACCH implementation helped the child demonstrate significant progress in emotional regulation, social interaction, and task independence, such as putting on shoes and organizing learning materials. The structured environment and consistent visual cues effectively reduced maladaptive behavior and enhanced the child's focus during class activities. This study highlights that the TEACCH method can be an effective psychological mentoring approach for increasing independence in children with autism, especially in inclusive elementary education settings.